Guidance Note on the Exogenous Shocks Facility. (Policy Papers; Policy Paper ;, 2006)
The ESF, established within the Poverty Reduction and Growth Facility and Exogenous Shocks Facility (PRGF-ESF) Trust, complements existing Fund instruments for providing timely support, including financing at more appropriate terms, to low-income members that are facing sudden and exogenous shocks but do not have a PRGF arrangement in place. In particular, the ESF: (i) facilitates quick access to more concessional financing than the Fund's Emergency Assistance and the Compensatory Financing Facility (CFF);1 (ii) helps members design and implement a policy framework adequate for adjustment to shocks while ensuring adequate safeguards for the use of the Trust resources; and (iii) plays a catalytic role for further and more concessional donor financing.